Optical Fibers Forming For Optical Sensors Research - Jelínek, Michal (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2018)
We present development of new methods and techniques of the splicing and shaping optical fibers with focusing to development new sensors. We developed new techniques of splicing for standard Single Mode (SM) and Multimode (MM) optical fibers and optical fibers with different diameters in the wavelength range from 532 to 1550 nm. Together with development these techniques we prepared other techniques to splicing and shaping special optical fibers like as Polarization-Maintaining (PM) or hollow core Photonic Crystal Fiber (PCF) and theirs cross splicing methods with focus to minimize backreflection and attenuation. Splicing special optical fibers, especially PCF fibers with standard telecommunication and other SM fibers, can be done by light adjustment of our developed techniques.
Keywords: microstructured fibers; optical sensors; shaping optical fibers; splicing optical fibers; tapering optical fibers